GENETIC VARIABILITY FOR GRAIN YIELD AND GRAIN QUALITY CHARACTERS IN MEDIUM AND LONG SLENDER VARIETIES OF RICE (Oryza sativa L.) - ZAKIR HUSSAIN, NARENDRA KULKARNI and (The Journal of Research, PJTSAU, 2017)
Variability, variety x season interactions and genetic components were estimated in long and medium slender grain rice varieties. There was increase in duration, number of tillers and grain yield in rabi season while there was decrease in plant height compared to kharif. The variance due to varieties, seasons and variety x season interactions for grain yield and its componentswere significant except variety x season for grain yield in long slender varieties. Variance due to season was of higher magnitude. Among the grain quantity characters heritability estimates ranged from 79.2 for milling to 95.3 percent for grain yield in long slender varieties. Heritability ranged from 66.8 for milling to 95.8 for grain length in medium slender varieties. Genetic advance was higherfor grain and kernel length in medium slender varieties which can be further improved by selection. Head rice recovery in both grain types had high heritability and genetic advance giving scope for further selection. Among long slender varieties RJ 78, RJ 93, RJ 99 and among medium slender varieties RJ 91, RJ 103, RJ 110 had higher yield and good grain quality attributes andappeared promising.